2005
DOI: 10.1111/j.1523-5378.2005.00315.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effects of Polyphenols on Gastric Injury by Helicobacter pylori VacA Toxin

Abstract: HBT may suppress the development of inflammation and ulceration caused by H. pylori VacA, suggesting that HBT may be useful as a new type of therapeutic agent for the prevention of gastric ulcer and inflammation caused by VacA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
34
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 38 publications
2
34
1
Order By: Relevance
“…In many cases, the antibacterial activity of both herbal extracts and foodstuffs has been associated with their content in phenolic compounds, in particular, flavonoids (11)(12)(13), resveratrol (6), and hydrolyzable tannins (14). The mechanism by which phenolic compounds affect the growth of H. pylori is unknown, but different theories have been proposed, for example, inhibition of the urease activity (15), adhesion to human gastric mucus (10), disintegration of the outer membrane (16), and inhibition of VacA citotoxin activity which causes the development of inflammation and ulceration in patients (17,18).…”
Section: Introductionmentioning
confidence: 99%
“…In many cases, the antibacterial activity of both herbal extracts and foodstuffs has been associated with their content in phenolic compounds, in particular, flavonoids (11)(12)(13), resveratrol (6), and hydrolyzable tannins (14). The mechanism by which phenolic compounds affect the growth of H. pylori is unknown, but different theories have been proposed, for example, inhibition of the urease activity (15), adhesion to human gastric mucus (10), disintegration of the outer membrane (16), and inhibition of VacA citotoxin activity which causes the development of inflammation and ulceration in patients (17,18).…”
Section: Introductionmentioning
confidence: 99%
“…We have previously found that polyphenols and polyphenol-rich beverages, such as tea and wine, inhibit VacA activity in vitro [12] , and that some polyphenols can limit both H pylori-and VacA-induced gastric damage in vivo [13] . Also, it has been recently reported that hop bract extract exerts anti-VacA activity in vitro and in vivo [14] . In the present paper we investigated whether red wine and green tea concentrates could influence gastric colonization or gastric pathology in H pylori-infected or VacA-treated mice.…”
Section: Introductionmentioning
confidence: 99%
“…Also, we have observed the ability of dealcoholized wine and green tea to reduce gastritis in mice experimentally infected by H. pylori (unpublished data). Hop bract extract has been recently reported to exert anti-VacA activity (35). Here, we investigated whether pure polyphenols could influence gastric colonization or gastritis in mice and/or counteract the effects of VacA in vivo.…”
mentioning
confidence: 99%